P421 Real-world effectiveness and safety of vedolizumab induction therapy for Crohn's disease in Poland – a prospective, observational POLONEZ II study considering patients reported outcomes. (30th January 2023) - Liebert, A; Kłopocka, M; Cichoż-Lach, H; Michalak, A; Talar-Wojnarowska, R; Domżał-Magrowska, D; Filipiuk, A; Krogulecki, M; Kopertowska-Majchrzak, M; Eder, P; Stawczyk-Eder, K; Waszak, K; et al.
Abstract: Background: Vedolizumab (VDZ) is a gut-selective anti-lymphocyte trafficking drug, used to treat ulcerative colitis (UC) and Crohn's disease (CD), lifelong conditions with unknown aetiology with frequent relapses and remitting course which are a burden for patients and a challenge for health care systems. We aimed to evaluate the real-world effectiveness of VDZ induction therapy for Polish patients with CD. Methods: This was a multicenter, observational, prospective study involving patients with moderately to severely active CD qualified for reimbursed treatment with VDZ in 10 Polish centers between Apr 2020 and Nov 2021. The primary endpoints were clinical response (≥ 70-point reduction in Crohn's Disease Activity Index, CDAI) and remission rate (CDAI ≤ 150) at week 14. Other endpoints included changes from baseline (week 0, first dose of VDZ) to week 14 for patient-reported outcomes (PROs): quality of life (Inflammatory Bowel Disease Questionnaire, IBDQ), fatigue (Inflammatory Bowel Disease-Fatigue Self-assessment Scale, IBD-F), stool frequency (SF score) and abdominal pain score (APS). Results: A total of 98 patients with CD were enrolled in the study. At baseline, the most common disease location in the cohort was ileocolonic CD (n=70/98, 72.9%). Fifty patients (51%) were on corticosteroids at week 0. Nine patients discontinued VDZ therapy before or at week 14, mainly due to lack of response (n=6/9, 66.7%). At week 14, 63.3% of patients (n=62/98) achieved clinical remission and 30% (n=15/50) steroid-free remission. Clinical response rate in overall study population was 90.8% (n=89/98). Median CDAI score decreased from 336.5 to 108.0 ( p <0.001) at week 14 (Fig. 1). Declines from baseline were also observed in median CDAI sub-scores: SF score (38.0 vs 10.0; p <0.001) and APS (18.0 vs 2.0; p <0.001) (Fig. 1). At week 14, median changes from baseline scores on the IBDQ (total and all subscales) were statistically significant ( p <0.001) (Fig. 2). Improvement was also observed after the VDZ 14-week treatment period in fatigue severity and frequency ( p <0.01) as well as its impact on daily activities ( p <0.001) based on IBD-F (Fig. 3). The percentage of patients without concomitant corticosteroids increased more than 1.5-fold from week 0 (49.0%) to week 14 (76.3%). Conclusion: VDZ is effective in induction therapy and has significant impact on disease activity and Health-Related Quality of Life (HRQL) including fatigue in patients with CD.